Graphene electrolytic diaphragm material and preparation method thereof

By combining modified vinyl chloride-acrylonitrile copolymer and modified graphene, graphene electrolytic separators are prepared, which solves the high current consumption and high cost of composite separators during metal nickel electrolysis, and achieves low-energy electrolytic production.

CN120519922AActive Publication Date: 2025-08-22ZHANGYE XILONG IND IS USED TEXTILE PROD CO LTD

Patent Information

Application Number
CN202511029156.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-25
Publication Date
2025-08-22
Estimated Expiration
2045-07-25

AI Technical Summary

Technical Problem

The existing composite separator materials have problems of high current consumption and high production costs during the electrolysis of metal nickel, and the hydrophobicity of the polyester filter cloth is not conducive to the infiltration of the electrolyte and the transmission of ions.

Method used

A glue solution composed of modified vinyl chloride-acrylonitrile copolymer, modified graphene, carbon nanotubes and polyvinylpyrazone is prepared by soaking and extruding the film to prepare a graphene electrolytic separator. The modified vinyl chloride-acrylonitrile copolymer introduces hydrophilic groups and benzene ring structures, and the modified graphene improves dispersion and forms molecular chain winding to reduce surface resistance.

Benefits of technology

It improves the hydrophilicity and conductivity of the diaphragm, reduces the surface resistance, reduces the interface tension of the electrolyte, promotes rapid penetration of the electrolyte, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a graphene electrolytic diaphragm material and a preparation method thereof, and belongs to the technical field of diaphragm materials. The preparation method comprises the following steps: S1, weighing the following components in parts by weight: 10 to 15 parts of a modified vinyl chloride-acrylonitrile copolymer, 60 to 65 parts of dimethylformamide, 15 to 25 parts of dimethyl sulfoxide, 6 to 8 parts of modified graphene, 0.4 to 0.5 part of a carbon nanotube and 1 to 2 parts of polyvinylpyrrolidone; s2, sequentially adding a modified vinyl chloride-acrylonitrile copolymer, dimethylformamide, dimethyl sulfoxide, modified graphene, carbon nanotubes and polyvinylpyrrolidone into a reaction tank, heating to 50-60 DEG C, and stirring and dissolving to prepare a glue solution; s3, immersing base cloth into the glue solution, extruding to form a film, soaking in a cold water pool, soaking in a hot water pool, and drying to obtain the product. The prepared electrolytic diaphragm material has good water absorption and low surface resistance, and the production cost of metal nickel can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of diaphragm materials, and in particular to a graphene electrolysis diaphragm material and a preparation method thereof. Background Art

[0002] Electrode diaphragms play a crucial role in the production of nickel electrowinning and electrorefining. They primarily separate the cathode and anode in the electrolytic cell, forming independent cathode and anode compartments. Currently used composite diaphragm bags are based on polyester filter cloth, which resists corrosion in strong acid and alkaline environments, including those found in enclosed, high-pressure, and high-temperature environments. However, filter cloth is an insulating material, consuming high current during the electrolysis process and resulting in high production costs. Furthermore, the hydrophobicity of polyester filter cloth hinders electrolyte wetting and ion transport. Therefore, developing composite diaphragm materials with excellent hydrophilicity and low electrical resistance to meet the production needs of low-energy nickel electrolysis is a key area of ​​research in electrolytic diaphragm materials.

[0003] Chinese invention patent publication number CN117051579A discloses a super-hydrophilic electrolytic cell diaphragm material and a preparation method thereof. The fiber material is pretreated and treated with low-temperature plasma, and then immersed in a TBT ethanol solution to obtain a fiber material with deposited titanium dioxide. The fiber material is then hydrolyzed, washed, and dried to obtain a super-hydrophilic electrolytic cell diaphragm material. This solution has readily available raw materials, a simple preparation process, and is easy to control, making it suitable for large-scale promotion and application. However, there is a risk of the deposited titanium dioxide falling off, thereby affecting the performance of the diaphragm. Summary of the Invention

[0004] In view of the shortcomings of the prior art, the object of the present invention is to provide a graphene electrolytic diaphragm material and a preparation method thereof.

[0005] To achieve the above object, the present invention is implemented through the following technical solutions: A method for preparing a graphene electrolytic diaphragm material comprises the following steps: S1: Weigh by weight: modified vinyl chloride-acrylonitrile copolymer: 10-15 parts, dimethylformamide: 60-65 parts, dimethyl sulfoxide: 15-25 parts, modified graphene: 6-8 parts, carbon nanotubes: 0.4-0.5 parts, polyvinyl pyrrolidone: 1-2 parts; S2: Add modified vinyl chloride-acrylonitrile copolymer, dimethylformamide, dimethyl sulfoxide, modified graphene, carbon nanotubes, and polyvinyl pyrrolidone into a reaction tank in sequence, heat to 50-60°C, and stir to dissolve to form a glue solution; S3: Immerse the base fabric in the adhesive solution, extrude it into a film, soak it in a cold water pool, soak it in a hot water pool, and dry it.

[0006] The modified vinyl chloride-acrylonitrile copolymer is prepared by the following method: M1: Polyethylene glycol reacts with acrylic acid to form a macromonomer; in this reaction, the terminal hydroxyl group of polyethylene glycol undergoes esterification with acrylic acid; M2: Dopamine reacts with epoxybutene to form a phenolic hydroxyl monomer; the reaction equation is as follows:

[0007] M3: Vinyl chloride, acrylonitrile, acrylic acid, macromonomer and phenolic hydroxyl monomer undergo free radical polymerization under the action of an initiator to generate a modified vinyl chloride-acrylonitrile copolymer.

[0008] In step M1, the molar ratio of the polyethylene glycol to the acrylic acid is (1-1.2):1.

[0009] In step M2, the molar ratio of dopamine to epoxybutene is 1:(1-1.3).

[0010] In step M3, the mass ratio of the vinyl chloride, acrylonitrile, acrylic acid, macromonomer and phenolic hydroxyl monomer is (7-8):(6-7):1:(10-12):(1.5-2).

[0011] The modified graphene is prepared by the following method: N1: Polyethylene glycol and but-1-enyl(trimethoxy)silane undergo addition reaction in the presence of catalyst C-94 and 1-butyl-3-methylimidazolium methanesulfonate ionic liquid to obtain modified polyethylene glycol; N2: Modified polyethylene glycol reacts with graphene oxide to obtain modified graphene, in which the silicon methoxy group reacts with the hydroxyl group on the surface of the graphene oxide to obtain the modified graphene.

[0012] In step N1, the mass ratio of the polyethylene glycol to but-1-enyl(trimethoxy)silane is 6:1.

[0013] In step N2, the mass ratio of the modified polyethylene glycol to the graphene oxide is 1:2.

[0014] The base fabric is polyester filter cloth.

[0015] A graphene electrolytic diaphragm material is prepared by the above method.

[0016] Due to the adoption of the above technical solution, the beneficial effects of the present invention include: (1) The modified vinyl chloride-acrylonitrile copolymer prepared by the present invention improves the hydrophilicity of the diaphragm and reduces the surface resistance of the diaphragm by introducing hydrophilic groups and benzene ring structures.

[0017] (2) The modified graphene prepared by the present invention improves the dispersibility of graphene and further reduces the surface resistance through molecular chain entanglement, thereby reducing the production cost of metal nickel electrolysis. DETAILED DESCRIPTION

[0018] The present invention will be further described below with reference to the embodiments, but the present invention is not limited to these embodiments.

[0019] Example 1 Preparation of modified vinyl chloride-acrylonitrile copolymer M1: Under nitrogen protection, 0.1 mol of acrylic acid and 0.1 mol of polyethylene glycol (PEG1000) were added to a reactor, heated to 60°C, and stirred at 1000 r / min for 30 min. 1 g of p-toluenesulfonic acid was added, and the temperature was raised to 80°C. The reaction was continued for 15 h (during which the water produced during the reaction was removed by a water separator). The reaction was cooled to room temperature, and 300 ml of n-hexane was added to stir and precipitate. The mixture was filtered and dried in a vacuum at 40°C for 24 h to obtain a macromonomer. M2: Under nitrogen protection, 100 ml of DMF and 0.1 mol of dopamine were added to a reactor, stirred and mixed, and the temperature was raised to 70°C. 50 ml of a DMF solution containing 0.1 mol of epoxybutene was added dropwise for 30 minutes. The reaction was allowed to proceed for 30 hours. The reaction solution was cooled to room temperature, poured into 200 ml of a pH = 3 HCl aqueous solution, filtered, and washed three times with deionized water (100 ml each time). The solution was then dried under vacuum at 60°C for 24 hours to obtain a phenolic hydroxyl monomer. Its H NMR spectrum data are as follows: 1 H NMR (500 MHz, Chloroform-d) δ 7.46(s, 1H), 6.77 - 6.63 (m, 2H), 6.50 (dt, J = 1.6, 0.8 Hz, 1H), 6.42 (s, 1H), 5.86 (dddt, J = 16.2, 10.7, 7.6, 0.9 Hz, 1H), 5.30 (dt, J = 16.2, 2.3 Hz,1H), 5.09 (dt, J = 10.7, 2.3 Hz, 1H), 4.29 - 4.11 (m, 2H), 3.10 - 2.90 (m,4H), 2.82 - 2.66 (m, 3H); M3: Under nitrogen protection, 1000 ml of dimethylacetamide, 70 g of vinyl chloride, and 60 g of acrylonitrile were added to the reactor, stirred for 30 min, heated to 60 ° C, 5 g of azobisisobutyronitrile was added and reacted for 12 h, 10 g of acrylic acid, 100 g of macromolecular monomer and 15 g of phenolic hydroxyl monomer were added, and the reaction was continued for 10 h. After cooling to room temperature, the mixture was filtered, washed twice with anhydrous ethanol (500 ml each time), and dried in vacuo at 60 ° C for 24 h to obtain a modified vinyl chloride-acrylonitrile copolymer.

[0020] Example 2 Preparation of modified vinyl chloride-acrylonitrile copolymer M1: Under nitrogen protection, 0.11 mol of acrylic acid and 0.1 mol of polyethylene glycol (PEG1000) were added to a reactor, heated to 60°C, and stirred at 1000 rpm for 30 min. 1 g of p-toluenesulfonic acid was added, and the temperature was raised to 90°C. The reaction was continued for 12 h (during which the water produced during the reaction was removed by a water separator). The reaction was cooled to room temperature, and 300 ml of n-hexane was added to stir and precipitate. The mixture was filtered and dried under vacuum at 40°C for 24 h to obtain a macromonomer. M2: Under nitrogen protection, 100 ml of DMF and 0.1 mol of dopamine were added to a reactor, stirred and mixed, and the temperature was raised to 80°C. 50 ml of a DMF solution containing 0.12 mol of epoxybutene was added dropwise for 30 minutes. The reaction was continued for 24 hours, and the mixture was cooled to room temperature. The reaction solution was poured into 200 ml of a pH = 3 HCl aqueous solution, filtered, and washed three times with deionized water (100 ml each time). The mixture was then dried under vacuum at 60°C for 24 hours to obtain a phenolic hydroxyl monomer. M3: Under nitrogen protection, 1000 ml of dimethylacetamide, 78 g of vinyl chloride, and 65 g of acrylonitrile were added to the reactor, stirred for 30 min, heated to 70 ° C, and 5 g of azobisisobutyronitrile was added to react for 10 h. 10 g of acrylic acid, 110 g of macromolecular monomer and 18 g of phenolic hydroxyl monomer were added and the reaction was continued for 10 h. The mixture was cooled to room temperature, filtered, washed twice with anhydrous ethanol (500 ml each time), and dried in a vacuum at 60 ° C for 24 h to obtain a modified vinyl chloride-acrylonitrile copolymer.

[0021] Example 3 Preparation of modified vinyl chloride-acrylonitrile copolymer M1: Under nitrogen protection, 0.12 mol of acrylic acid and 0.1 mmol of polyethylene glycol (PEG1000) were added to a reactor, heated to 60°C, stirred at 1000 r / min for 30 min, 1 g of p-toluenesulfonic acid was added, and the temperature was raised to 100°C. The reaction was continued for 10 h, during which the water produced during the reaction was removed through a water separator. The reaction was cooled to room temperature, and 300 ml of n-hexane was added to stir and precipitate. The mixture was filtered and dried in a vacuum at 40°C for 24 h to obtain a macromonomer. M2: Under nitrogen protection, 100 ml of DMF and 0.1 mol of dopamine were added to a reactor, stirred and mixed, and the temperature was raised to 90°C. 50 ml of a DMF solution containing 0.13 mol of epoxybutene was added dropwise for 30 minutes. The reaction was continued for 20 hours, and the mixture was cooled to room temperature. The reaction solution was poured into 200 ml of a pH = 3 HCl aqueous solution, filtered, and washed three times with deionized water (100 ml each time). The mixture was dried under vacuum at 60°C for 24 hours to obtain a phenolic hydroxyl monomer. M3: Under nitrogen protection, 1000 ml of dimethylacetamide, 80 g of vinyl chloride, and 70 g of acrylonitrile were added to the reactor, stirred for 30 min, heated to 80 ° C, and 5 g of azobisisobutyronitrile was added to react for 10 h. 10 g of acrylic acid, 120 g of macromonomer and 20 g of phenolic hydroxyl monomer were added to continue the reaction for 10 h. The mixture was cooled to room temperature, filtered, washed twice with anhydrous ethanol (500 ml each time), and dried in vacuo at 60 ° C for 24 h to obtain a modified vinyl chloride-acrylonitrile copolymer.

[0022] Example 4 Preparation of modified graphene N1: Under nitrogen protection, 600 ml of DMF, 60 g of polyethylene glycol (PEG1000), 10 g of but-1-enyl(trimethoxy)silane, 3 g of catalyst C-94, and 1 g of 1-butyl-3-methylimidazolium methanesulfonate ionic liquid were added to the reactor in sequence. The temperature was raised to 100°C and the reaction was carried out for 5 h. The temperature was then cooled to room temperature. 500 ml of deionized water was added and stirred to precipitate the solid. The solid was filtered, washed with 200 ml of anhydrous ethanol and 200 ml of deionized water in sequence, and dried in vacuo at 80°C for 10 h to obtain the modified polyethylene glycol. N2: 800 ml of anhydrous ethanol, 50 g of modified polyethylene glycol, and 100 g of graphene oxide were added to a reaction flask in sequence, the temperature was raised to reflux, the reaction was carried out for 24 h, the mixture was cooled to room temperature, filtered, and vacuum dried at 50 °C for 12 h to obtain modified graphene.

[0023] Example 5 Preparation of graphene electrolytic diaphragm material S1: Weigh: 100 g of modified vinyl chloride-acrylonitrile copolymer (prepared in Example 1), 600 g of dimethylformamide, 150 g of dimethyl sulfoxide, 60 g of modified graphene (prepared in Example 4), 4 g of carbon nanotubes, and 10 g of polyvinyl pyrrolidone; S2: Add modified vinyl chloride-acrylonitrile copolymer, dimethylformamide, dimethyl sulfoxide, modified graphene, carbon nanotubes, and polyvinyl pyrrolidone into a reaction tank in sequence, heat to 50°C, and stir to dissolve to form a glue solution; S3: inject the glue solution into the laminating tank, start the linked laminating machine, immerse the polyester filter cloth into the glue tank through the guide rack at a speed of 1.5m / min, and after being rolled by the squeezing roller (pressure 20MPa) to form a film, immerse it in a 0℃ cold water pool for 15min, then immerse it in a 60℃ hot water pool for 15min, and finally dry it at 80℃ for 2h.

[0024] Example 6 Preparation of graphene electrolytic diaphragm material S1: Weigh: modified vinyl chloride-acrylonitrile copolymer (prepared in Example 2): 120 g, dimethylformamide: 620 g, dimethyl sulfoxide: 220 g, modified graphene (prepared in Example 4): 70 g, carbon nanotubes: 4.5 g, and polyvinyl pyrrolidone: 18 g; S2: Add modified vinyl chloride-acrylonitrile copolymer, dimethylformamide, dimethyl sulfoxide, modified graphene, carbon nanotubes, and polyvinyl pyrrolidone into a reaction tank in sequence, heat to 55°C, and stir to dissolve to form a glue solution; S3: inject the glue solution into the laminating tank, start the linked laminating machine, immerse the polyester filter cloth into the glue tank through the guide rack at a speed of 1.5m / min, and after being rolled by the squeezing roller (pressure 20MPa) to form a film, immerse it in a 0℃ cold water pool for 15min, then immerse it in a 60℃ hot water pool for 15min, and finally dry it at 80℃ for 2h.

[0025] Example 7 Preparation of graphene electrolytic diaphragm material S1: Weigh: modified vinyl chloride-acrylonitrile copolymer (prepared in Example 3): 150 g, dimethylformamide: 650 g, dimethyl sulfoxide: 250 g, modified graphene (prepared in Example 4): 80 g, carbon nanotubes: 5 g, polyvinyl pyrrolidone: 20 g; S2: Add modified vinyl chloride-acrylonitrile copolymer, dimethylformamide, dimethyl sulfoxide, modified graphene, carbon nanotubes, and polyvinyl pyrrolidone into a reaction tank in sequence, heat to 60°C, and stir to dissolve to form a glue solution; S3: inject the glue solution into the laminating tank, start the linked laminating machine, immerse the polyester filter cloth into the glue tank through the guide rack at a speed of 1.5m / min, and after being rolled by the squeezing roller (pressure 20MPa) to form a film, immerse it in a 0℃ cold water pool for 15min, then immerse it in a 60℃ hot water pool for 15min, and finally dry it at 80℃ for 2h.

[0026] Comparative Example 1 The preparation method of the graphene electrolytic diaphragm material is basically the same as that of Example 6, except that the modified vinyl chloride-acrylonitrile copolymer (prepared in Example 2) is replaced by an equal mass of modified vinyl chloride-acrylonitrile copolymer prepared by the following method: The preparation method of the modified vinyl chloride-acrylonitrile copolymer is basically the same as that of Example 2, except that acrylic acid is not added in step M3.

[0027] Comparative Example 2 The preparation method of the graphene electrolytic diaphragm material is basically the same as that of Example 6, except that the modified vinyl chloride-acrylonitrile copolymer (prepared in Example 2) is replaced with an equal mass of modified vinyl chloride-acrylonitrile copolymer prepared by the following method: The preparation method of the modified vinyl chloride-acrylonitrile copolymer is basically the same as that of Example 2, except that the dopamine in step M2 is replaced by an equal molar amount of 2-amino-1,3-propanediol.

[0028] Comparative Example 3 The preparation method of the graphene electrolytic diaphragm material is basically the same as that of Example 6, except that the modified vinyl chloride-acrylonitrile copolymer (prepared in Example 2) is replaced with an equal mass of modified vinyl chloride-acrylonitrile copolymer prepared by the following method: Under nitrogen protection, 1000 ml of dimethylacetamide, 78 g of vinyl chloride, and 65 g of acrylonitrile were added to a reactor, stirred for 30 min, heated to 70°C, and 5 g of azobisisobutyronitrile was added and reacted for 10 h. 10 g of acrylic acid and 18 g of phenolic hydroxyl monomer (prepared in Step M2 of Example 2) were added and the reaction was continued for 10 h. The mixture was cooled to room temperature, filtered, washed twice with anhydrous ethanol (500 ml each time), and dried in vacuo at 60°C for 24 h to obtain a modified vinyl chloride-acrylonitrile copolymer.

[0029] Comparative Example 4 The preparation method of the graphene electrolytic diaphragm material is basically the same as that of Example 6, except that the modified graphene (prepared in Example 4) is replaced with an equal mass of modified graphene prepared by the following method: The preparation method of modified graphene is basically the same as that of Example 4, except that the but-1-enyl(trimethoxy)silane in step N1 is replaced by an equal mass of allyltrimethoxysilane.

[0030] Comparative Example 5 The preparation method of the graphene electrolytic diaphragm material is basically the same as that of Example 6, except that the modified graphene (prepared in Example 4) is replaced with an equal mass of modified graphene prepared by the following method: The preparation method of modified graphene is basically the same as that of Example 4, except that the polyethylene glycol (PEG1000) in step N1 is replaced by polyethylene glycol (PEG500) of equal mass.

[0031] Comparative Example 6 The preparation method of the graphene electrolytic diaphragm material is basically the same as that of Example 6, except that the modified graphene (prepared in Example 4) is replaced with an equal mass of modified graphene prepared by the following method: The preparation method of modified graphene is basically the same as that of Example 4, except that the polyethylene glycol (PEG1000) in step N1 is replaced by polyethylene glycol (PEG2000) of equal mass.

[0032] The graphene oxide used in the examples and comparative examples of the present application is model SE243EW, with a solid content of 42 wt%, produced by Changzhou Sixth Element Materials Technology Co., Ltd.; the carbon nanotube model is GT-301, produced by Shandong Dazhan Nanomaterials Co., Ltd.; the polyvinyl pyrrolidone is PVP K30; and the polyester filter cloth model is T6220-5×5 (warp density: 62 roots / inch, weft density: 20 roots / inch, warp yarn 21s / 5, weft yarn 21s / 5; square meter weight 500g).

[0033] The membrane materials prepared in Examples 5-7 and Comparative Examples 1-6 were subjected to a water absorption test according to GB / T 21655.1-2008 and a surface resistance test according to SJ / T 10171.5-1991. The test results are shown in Table 1.

[0034] Table 1 Performance test data table From the data of Examples 5, 6 and 7 in Table 1, it can be seen that the electrolytic diaphragm material prepared by the present invention has good water absorption and low surface resistance, improves the conductivity of the diaphragm cloth, thereby increasing the migration speed of metal ions in the electrolyte, thereby reducing production costs.

[0035] The graphene electrolytic diaphragm material prepared by the present invention has good water absorption and low surface resistance. The reasons are as follows: the modified vinyl chloride-acrylonitrile copolymer prepared by the present invention contains carboxyl groups and polyethylene glycol segments, and its hydrophilicity can reduce the interfacial tension between the electrolyte and the diaphragm, and promote the rapid penetration of the electrolyte into the pores; the catechol structure and benzene ring structure in the modified vinyl chloride-acrylonitrile copolymer can form hydrogen bonds with polar groups on the surface of the polyester filter cloth or achieve adhesion through π-π stacking, thereby preventing the cloth from falling off during use; and the benzene ring and graphene can form continuous electron channels through π-π stacking, reducing the energy barrier for electron migration across the interface, thereby achieving the effect of reducing surface resistance.

[0036] The modified graphene prepared by the present invention is obtained by grafting graphene oxide with silanized polyethylene glycol, thereby improving the dispersibility of graphene in the glue. The polyethylene glycol segments of the modified graphene and the polyethylene glycol segments of the modified vinyl chloride-acrylonitrile copolymer are entangled with each other, thereby improving the dispersibility of the graphene material and reducing the surface resistance. In addition, the two-dimensional graphene and the one-dimensional carbon nanotubes are combined to form a three-dimensional conductive network, thereby improving the conductivity. Comparative Example 4 uses allyltrimethoxysilane to modify graphene oxide, which has a smaller steric hindrance, resulting in slightly poor graphene dispersibility and a slightly increased surface resistance. The low molecular weight of the polyethylene glycol segment has a weak steric hindrance effect and cannot effectively inhibit the aggregation of graphene sheets, resulting in obstruction of the electron transmission path; when the molecular weight of the polyethylene glycol segment is too high, an excessively thick insulating layer is formed on the graphene surface, which increases the electron tunneling barrier and increases the surface resistance.

[0037] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. However, any equivalent changes, modifications and evolutions made by ordinary technicians in this field without departing from the scope of the technical solution of the present invention by using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing a graphene electrolytic diaphragm material, characterized in that: The following steps are involved: S1: Weigh by weight: modified vinyl chloride-acrylonitrile copolymer: 10-15 parts, dimethylformamide: 60-65 parts, dimethyl sulfoxide: 15-25 parts, modified graphene: 6-8 parts, carbon nanotubes: 0.4-0.5 parts, polyvinyl pyrrolidone: 1-2 parts; S2: Add modified vinyl chloride-acrylonitrile copolymer, dimethylformamide, dimethyl sulfoxide, modified graphene, carbon nanotubes, and polyvinyl pyrrolidone into a reaction tank in sequence, heat to 50-60°C, and stir to dissolve to form a glue solution; S3: Immerse the base fabric in the adhesive solution, extrude it into a film, soak it in a cold water pool, soak it in a hot water pool, and dry it.

2. The method for preparing a graphene electrolytic diaphragm material according to claim 1, wherein: The modified vinyl chloride-acrylonitrile copolymer is prepared by the following method: M1: Polyethylene glycol reacts with acrylic acid to form a macromonomer; M2: Dopamine reacts with epoxybutene to form a phenolic hydroxyl monomer; M3: Vinyl chloride, acrylonitrile, acrylic acid, macromonomer and phenolic hydroxyl monomer react under the action of an initiator to form a modified vinyl chloride-acrylonitrile copolymer.

3. The method for preparing a graphene electrolytic diaphragm material according to claim 2, wherein: In step M1, the molar ratio of the polyethylene glycol to the acrylic acid is (1-1.2):

1.

4. The method for preparing a graphene electrolytic diaphragm material according to claim 2, wherein: In step M2, the molar ratio of dopamine to epoxybutene is 1:(1-1.3).

5. The method for preparing a graphene electrolytic diaphragm material according to claim 2, wherein: In step M3, the mass ratio of the vinyl chloride, acrylonitrile, acrylic acid, macromonomer and phenolic hydroxyl monomer is (7-8):(6-7):1:(10-12):(1.5-2).

6. The method for preparing a graphene electrolytic diaphragm material according to claim 1, wherein: The modified graphene is prepared by the following method: N1: Polyethylene glycol and but-1-enyl(trimethoxy)silane react in the presence of catalyst C-94 and 1-butyl-3-methylimidazolium methanesulfonate ionic liquid to obtain modified polyethylene glycol; N2: Modified polyethylene glycol and graphene oxide react to obtain modified graphene.

7. The method for preparing a graphene electrolytic diaphragm material according to claim 6, wherein: In step N1, the mass ratio of the polyethylene glycol to but-1-enyl(trimethoxy)silane is 6:

1.

8. The method for preparing a graphene electrolytic diaphragm material according to claim 6, wherein: In step N2, the mass ratio of the modified polyethylene glycol to the graphene oxide is 1:

2.

9. The method for preparing a graphene electrolytic diaphragm material according to claim 1, wherein: The base fabric is polyester filter cloth.

10. A graphene electrolytic diaphragm material, characterized in that: Prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Hydrosilylation method for modifying graphene

    CN102730674A

  • Polyvinyl chloride graft copolymers

    GB1050781A

  • Smart acid value measuring apparatus

    KR102797372B1

  • Method for preparing multifunctional graphene oxide and method for preparing pvcpvdf composite film

    WO2024031541A1

Cited By

  • Composite diaphragm material for electrolysis and preparation process thereof

    CN120816784A